1997
DOI: 10.1021/jp9724784
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Investigation of Si-TPA-MFI Crystallization Using (Ultra-) Small- and Wide-Angle X-ray Scattering

Abstract: The formation of precursors and the growth and aggregation of silicalite-1 crystals using tetrapropylammonium as a template (Si-TPA-MFI) has been studied in situ using X-ray scattering techniques. Simultaneous smallangle and wide-angle X-ray scattering (respectively SAXS and WAXS) experiments using synchrotron light showed that the formation of amorphous colloidal aggregates in water clear synthesis mixtures was dependent on the alkalinity of the solutions. In situ time-resolved ultra-small-angle X-ray scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 41 publications
8
108
1
Order By: Relevance
“…Long-range order is attained in a consecutive layer-by-layer zeolite growth step. This proposed formation mechanism is in agreement with results of an in situ SAXS and WAXS study by de Moor et al [15] of the same system. Their results show the initial formation of colloidal amorphous aggregates, which are not organized further in a secondary aggregation step, but instead, redissolve and act as a source of nutrients for the growing crystallites.…”
Section: Synthetic Aspects: Template Theory For Zeolite Synthesissupporting
confidence: 92%
See 2 more Smart Citations
“…Long-range order is attained in a consecutive layer-by-layer zeolite growth step. This proposed formation mechanism is in agreement with results of an in situ SAXS and WAXS study by de Moor et al [15] of the same system. Their results show the initial formation of colloidal amorphous aggregates, which are not organized further in a secondary aggregation step, but instead, redissolve and act as a source of nutrients for the growing crystallites.…”
Section: Synthetic Aspects: Template Theory For Zeolite Synthesissupporting
confidence: 92%
“…The aforementioned studies involve in situ IR, 29 Si NMR and X-ray scattering techniques, [13][14][15]17] although only the gel stage of the zeolite formation process was covered in these cases. The next step is the study of the crystallization process for these microporous materials, and indeed several research groups have reported such in situ investigations.…”
Section: Synthetic Aspects: Template Theory For Zeolite Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In their current configurations, neither of the above cell types (capillary or autoclave) is particularly suited to study the early stages of FeS nucleation reactions. Rather, other synchrotron-based techniques such as simultaneous SAXS-WAXS (small-and wide-angle X-ray scattering, respectively) experiments may make a contribution to our understanding of these reactions (de Moor et al 1997, Shaw et al 2000c.…”
Section: Results Of Synchrotron (Nsls) Powder-diffraction Of Fes → Fementioning
confidence: 99%
“…85%) have the size of 11.9 nm beside a small amount of larger sol particles with the size of 100 nm generated from the rapid hydrolysis and condensation processes of TEOS and Al(i-OPr) 3 in alkaline solution. de Moor et al [22,23] observed two types of precursor particles (2.8 nm sized primary units and ~10 nm aggregates) in MFI zeolite synthesis systems by small-angle X-ray scattering. Based on these results, sol particles can be thought reasonably to be aggregates of zeolite primary units.…”
Section: Particle Size Distribution Of Mfi Zeolite Precursor Solmentioning
confidence: 99%